Reliability of the Physical Activity Enjoyment Scale Questionnaire in Indian College Girl Students Population (International Journal of Food and Nutritional Sciences, 2023)
The study focuses on evaluating the reliability and psychometricproperties of the Physical Activity Enjoyment Scale (PACES-15)within a population of female college students in India. Given thelinguistic and cultural diversity in the country, there is a need forIndian-specific insights into the scale